Systemic dissemination of chronic necrotizing pulmonary aspergillosis in an elderly woman without comorbidity: a case report - Tokui, Kotaro (BioMed Central, 2012)
INTRODUCTION: Chronic necrotizing pulmonary aspergillosis usually occurs in mildly immune-compromised hosts or those with underlying pulmonary disease. The radiographic pattern of chronic necrotizing pulmonary aspergillosis is typically a progressive upper lobe cavitary infiltrate with pleural thickening. We report here an atypical case of chronic necrotizing pulmonary aspergillosis mimicking lung cancer, which developed into a disseminated fatal disease in an older woman with no comorbidity. CASE PRESENTATION: An 80-year-old Japanese woman was referred to our hospital for a chest roentgenogram abnormality. Repeated fiber-optic bronchoscopy could not confirm any definite diagnosis, and she refused further examinations. Considering the roentgenogram findings and her age, she was followed-up as a suspected case of lung cancer without any treatment. Then, 10 months later, she complained of visual disturbance and was admitted to our department of ophthalmology. She was diagnosed as having endophthalmitis. After treatment with corticosteroids for 20 days, she developed acute encephalitis and died four weeks later. Autopsy revealed dissemination of Aspergillus hyphae throughout her body, including her brain. CONCLUSIONS: In older patients, even if they do not have any comorbidity, chronic necrotizing pulmonary aspergillosis should be added to the differential diagnosis of solitary pulmonary lesions in a chest roentgenogram.